Spatial Analysis to Estimate Runaff Using Scs (CN) to Wadi Al mur Watershed North of Iraq - Dali Khalaf Hameed (Tikrit Journal of Pure Science, 2023)
The study aims at analyzing spatial and DEM data by the use of ArcGis, WMS, Global Mapper, and Erdas programas for finding hydrological Such data as climate and soil components have been analysed ,in addition to the classification of soil utilization and soil covering. The present study concludes by the use of the American soil conservation Service hypothesis SCS) which is known as Curve Number (CN)through the integrating of Remote Sensing (RS)technigue and the GIS to evaluate the water flow rate (QV) at times of rainfall (40185278 m3/ per – year).Implementing this model shows that the basin of Wadi Almur has such hydrological conditions that help in generating water flow in times of rainfall clue to the rise of(CN)value when isabout (81,86).